2009
DOI: 10.1242/dev.037267
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin3a regulates endothelial cell number and podocyte differentiation during glomerular development

Abstract: *Semaphorin3a (Sema3a), a chemorepellant guidance protein, plays crucial roles in neural, cardiac and peripheral vascular patterning. Sema3a is expressed in the developing nephron, mature podocytes and collecting tubules. Sema3a acts as a negative regulator of ureteric bud branching, but its function in glomerular development has not been examined. Here we tested the hypothesis that Sema3a regulates glomerular vascular development using loss-and gain-of-function mouse models. Sema3a deletion resulted in defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
101
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 63 publications
3
101
1
Order By: Relevance
“…Ostensibly because of genetic heterogeneity due to different maintenance this was not observed in another colony of Sema3a null CD-1 mice (Vieira et al, 2007). However, in further support for a role of SEMA3A in vascular remodeling, it has been recently reported that Sema3a deletion in an inbred strain results in defective renal vascular patterning (Reidy et al, 2009). Notably, in the same Sema3a null mice both Sema3b and Sema3e mRNA were found to be up-regulated (Reidy et al, 2009), thus providing a molecular mechanism by which compensation can occur in Sema3a null mice (Vieira et al, 2007).…”
Section: Semaphorins and Vascular Developmentmentioning
confidence: 95%
“…Ostensibly because of genetic heterogeneity due to different maintenance this was not observed in another colony of Sema3a null CD-1 mice (Vieira et al, 2007). However, in further support for a role of SEMA3A in vascular remodeling, it has been recently reported that Sema3a deletion in an inbred strain results in defective renal vascular patterning (Reidy et al, 2009). Notably, in the same Sema3a null mice both Sema3b and Sema3e mRNA were found to be up-regulated (Reidy et al, 2009), thus providing a molecular mechanism by which compensation can occur in Sema3a null mice (Vieira et al, 2007).…”
Section: Semaphorins and Vascular Developmentmentioning
confidence: 95%
“…Various growth factor/receptor signaling pathways, including FGFs, bone morphogenic proteins, VEGF, semaphorins, hepatocyte growth factor, EGF, among others, share signaling components with the c-Ret pathway and are required for optimal metanephric growth and patterning (15)(16)(17)(18)(19)(20)(21)(22). Following induction of the MM, activation of the Wnt/␤-catenin signaling pathway plays a key role in nephrogenesis.…”
mentioning
confidence: 99%
“…64 Furthermore, it has been suggested that there is functional competition between sema3a and VEGF. 65 Therefore, it is possible that Tak1 deletion-induced overexpression of VEGF suppresses the function of sema3a that leads to multiple endothelial cell defects.…”
Section: Discussionmentioning
confidence: 99%